Optimalisasi Potensi Wisata Alam dan Budaya Melalui Pemberdayaan Masyarakat Desa Ciasmara, Bogor - Reza Amandha Wulandari; Naufal Mustaqim; Akmal Maulida Sasmita; Natasya Adlia Putri Utami; Viery Salsaputra Triana; Kayla Rizky Amalia Putri; Alifia Khoirunnisa; Rayhan Ali Alfharidzi; Dicky Arya Arjuna Syukur; Utiya Rahma Fitri; Lizzilmi Syarifatuz Zaimah; Syekha Divani Fatihah; Soraya Azzahrah; Fahri Rizaldi; Wulan Ari Kartika; Puji Rianti (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Ciasmara Village, located in Bogor Regency, is one of the villages rich in natural and cultural potential. Currently, Ciasmara Village has more than five natural tourism sectors, one of which is the Curug Gleweran Cikawah sector. The Pancawarna Tourism Awareness Group (Pokdarwis) has been working to develop the Curug Gleweran Cikawah natural tourism area. However, a shortage of human resources has become a challenge in advancing this tourism sector. Additionally, Ciasmara Village also boasts unique traditional arts, including the celempung and karinding musical instruments, with practitioners known as the Dangiang Asmara Group. Besides Dangiang Asmara, only a few people are interested in preserving these arts, leading to limited efforts to protect local culture. The Bumi Luhur Program was designed to empower the community through the development of natural and cultural tourism potential. The program has five main components: 1) Sobat Bumi, training for tourism managers; 2) Bumi Priangan, the construction of a cultural center; 3) Bumi Alir, the building of a Micro Hydro Power Plant (PLTMH); 4) Bumi Asri, the creation of camping grounds; and 5) Bumi Napak, the revitalization of hiking trails. During the activities, initial stages included surveys and interviews, followed by implementation phases such as pre- and post-tests, land mapping, procurement of construction materials, installation, and monitoring. The program resulted in natural and cultural tourism sites with self-sufficient energy facilities. Enhanced human resource capacity through training, preserved celempung and karinding art through an approach targeting children, and increased tourist data, which impacted the income of the Ciasmara Village community in the Gleweran Cikawah sector.